Production Recommendations and Information Source Utilization of Rapeseed Mustard Growers in Sub-tropics of Kathua District in Jammu Division. - P. S. Slathia , Rakesh Nanda , RajinderPeshin , Laxmikant , S. K. Gupta , Rakesh Kumar and Raj Kumar, (Indian Journal of Extension Education, 2015)
Oilseed plays an important role in agriculture economy in many regions of the world. Oilseed is a major source ofprotein and contributes considerably to the export earnings. Major oilseed producing countries in the world areUSA, Brazil, Argentina, China and India and account for 82 per cent of oilseed production in the world. In thecategory of oilseed crops, rapeseed mustard is grown in both the regions of J&K state. In Jammu division, rapeseedmustard is grown in Sub-tropical and temperate agro-climatic zones. The present investigation was carried out tostudy the adoption of production recommendations of rapeseed mustard in the subtropical zone of Kathua district. Alist of 522 mustard growers was procured from Department of Agriculture of Kathua district and 95 respondentswere selected randomly with the help of random number generator. A comprehensive data collection tool wasdevised for collection of data. After pretesting and needful modifications the data was collected from selected 95respondents. It has been concluded from the study that toria is the main rapeseed mustard crop grown by the farmersof the study area and all the respondents were using their own seed and they were of the view that toria crop raised byusing own seed attains early maturity which does not hamper the timely sowing of wheat crop. It has been observedthat farmers of the study area are not adopting the recommended seed rate and none of the farmers are adopting seedtreatment. Regarding chemical fertilizers, farmers are not using potassic fertilizer for growing rapeseed mustardcrops. Department of agriculture and co-farmers are the main sources of agri-input information.